A study on cytology of soft tissue spindle cell tumors with histopathological correlation wherever possible - Dhanya K.; Sateesh Chavan S (Tropical Journal of Pathology and Microbiology, 2019)
Introduction: Spindle cell tumors constitute an important component of soft tissue tumors. Fine needle aspiration cytology provides a predictive diagnosis of type and nature of these neoplasms.Methods: This study was conducted for a period of four years.Results: A total of 124 cases were diagnosed as soft tissue spindle cell tumors cytologically. Of these, 86 (69.35%) cases were benign and 38 (30.64%) were malignant tumors. 52 cases were available for histopathological follow up of which 49 cases (94.23%) showed positive correlation. Though there are no specific tissue architectural patterns in cytological smears, they are helpful in providing predictive diagnosis of benign or malignant nature of the tumour and in many cases also of specific tumor type. However, histopathology is considered as “gold standard” in diagnosing spindle cell tumors. Ancillary techniques are helpful in providing definitive diagnosis thus increasing the diagnostic accuracy of FNAC. There were 2 false negative cases which were cytologically diagnosed as Schwannoma and Neurofibroma because of the presence of wavy spindle cells and blood but both cases were diagnosed as malignant peripheral nerve sheath tumor on histopathology. There was 1 false positive case cytologically diagnosed as malignant spindle cell tumor but histopathologically diagnosed as Pleomorphic lipoma.Conclusion: Cytological and histopathological correlation was available in 36 benign tumors and 16 malignant tumors. Among benign tumors, 94.44% (34 cases) showed positive correlation, 5.56% (2 cases) showed negative correlation. Whereas among malignant tumors, 93.75% (15 cases) showed positive correlation and 6.25% (1 case) showed negative correlation between cytologic and histopathologic diagnosis.